A tantalum-based oral guided bone regeneration barrier membrane and a preparation method thereof
Patent Information
- Application Number
- CN202311493120.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-09
AI Technical Summary
可吸收膜虽然避免了二次手术取出,但膜降解速度过快,降解周期与骨再生周期无法精准匹配,力学稳定性较差;聚四氟乙烯膜的力学强度低,成骨特性不佳;钛网的空间维持作用较好,但钛网的硬度较高使得术中不易剪裁操作,柔顺性不足使得对周围软组织的刺激较大,因暴露引起的失败案例在临床中比例较高
[0046]1、本发明实施例提供的屏障膜由钽基金属制备而成,钽具有很好的生物相容性和化学稳定性,能够保证屏障膜在植入期间不与人体产生反应,避免了膜结构的破坏或者释放出对人体有害的物质;除了纯钽,添加合金元素钛和钨可提高材料强度,添加铜可提高材料抗菌性,添加铌可提高材料的抗氧化性,上述钽合金同样具有很好的生物相容性和化学稳定性;
Smart Images

Figure CN117462765B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of medical devices, and in particular to a tantalum-based oral cavity guided bone regeneration barrier membrane and its preparation method. Background Technology
[0002] Dental implant restoration is the preferred treatment option for patients with missing teeth. Successful implant restoration requires sufficient alveolar bone quality and volume. Insufficient bone volume in the implant area due to trauma, tumor resection, inflammation, etc., is the primary reason for implant failure or failure. Guided Bone Regeneration (GBR) has become an effective method for restoring alveolar bone tissue in bone defect areas and improving the success rate of implant restoration. Because bone tissue grows more slowly than surrounding fibrous tissue and other soft tissues, without intervention, soft tissue will occupy the bone defect space during the restoration process, hindering bone regeneration. The key to GBR is to create a barrier membrane at the bone defect site, isolating it from soft tissue. This barrier membrane prevents soft tissue cells from growing into the defect area, ensuring the growth of slower-proliferating osteoblasts and blood vessels, creating a relatively stable space for bone regeneration, and achieving the expected bone increase.
[0003] Based on their degradation characteristics, barrier membranes can be divided into two main categories: non-absorbable membranes and absorbable membranes. Currently, the non-absorbable membranes used clinically are mainly polytetrafluoroethylene (PTFE) membranes and titanium meshes, while absorbable membranes are primarily animal collagen membranes. For large bone defects, sufficient mechanical properties are needed to maintain a stable barrier space. Although absorbable membranes avoid secondary surgical removal, their rapid degradation rate and the inability to precisely match the degradation cycle with the bone regeneration cycle result in poor mechanical stability. PTFE membranes have low mechanical strength and poor osteogenic properties. Titanium meshes offer better space maintenance, but their high rigidity makes them difficult to cut during surgery, and their lack of flexibility leads to significant irritation to surrounding soft tissues, resulting in a high proportion of surgical failures due to exposure. Summary of the Invention
[0004] To address the aforementioned problems, one objective of this invention is to provide a tantalum-based oral cavity guiding bone regeneration barrier membrane, which has advantages such as good mechanical stability, good flexibility, easy intraoperative cutting, good biocompatibility and osteoinductive properties, and better osteogenic and antibacterial effects. Another objective of this invention is to provide a method for preparing a tantalum-based oral cavity guiding bone regeneration barrier membrane, thereby addressing the current situation where tantalum-based metals are rarely used in the field of guiding bone regeneration barrier membranes and where process research is lacking.
[0005] One of the objectives of this invention is achieved through the following technical solution:
[0006] A tantalum-based oral cavity-guided bone regeneration barrier membrane, wherein the barrier membrane is made of tantalum-based metal, including pure tantalum and tantalum alloys; wherein...
[0007] The alloying elements in the tantalum alloy include at least one of niobium, titanium, molybdenum, copper, zinc, tungsten, and hafnium;
[0008] The thickness of the barrier membrane is 1μm-30μm.
[0009] As one preferred embodiment, when the alloying element is niobium, the barrier film, by mass percentage, comprises 55%-100% (but not 100%) tantalum and 0%-45% (but not 0%) niobium; or,
[0010] When the alloying element is titanium, the barrier film, by mass percentage, comprises 70%-100% (but not 100%) tantalum and 0%-30% (but not 0%) titanium; or,
[0011] When the alloying element is molybdenum, copper, zinc, tungsten or hafnium, the barrier film, by mass percentage, includes 90%-100% (but not 100%) tantalum and 0%-10% (but not 0%) alloying elements.
[0012] As one of the preferred embodiments, the barrier membrane has multiple through holes, each with a diameter of 1μm-20μm.
[0013] As one preferred embodiment, the plurality of through-holes are located in areas of the barrier membrane other than the central region, wherein the central region has a regular hexagonal shape; and
[0014] Multiple through-holes form several microporous units, each microporous unit having a regular hexagonal shape. The diameter of the inscribed circle of the regular hexagonal microporous unit is 1mm-1.5mm, and the spacing between two adjacent microporous units is 200μm-400μm; and,
[0015] The spacing between two adjacent through holes within each microporous unit is 30μm-60μm.
[0016] As one preferred embodiment, a metal frame is welded onto the barrier membrane, and the metal frame is made of the tantalum-based metal;
[0017] The metal frame has a thickness of 50μm-100μm and a width of 1mm-2mm.
[0018] As one of the preferred options, the metal frame includes any one or a combination of multiple types of straight, double-¥, double-¥ and double-wood types.
[0019] As one preferred embodiment, the surface of the barrier membrane is coated with a biodegradable polymer coating, a ceramic coating, or a drug coating; wherein,
[0020] The biodegradable polymer coating is made of at least one of the following materials:
[0021] Polycaprolactone, polylactic acid, polyhydroxyacetic acid, L-polylactic acid, polycyanoacrylate, polyanhydride, polyphosphononitrile, polydioxane, polyhydroxybutyrate, polyhydroxyvalerate and chitosan;
[0022] The ceramic coating is made of at least one of the following materials:
[0023] Hydroxyapatite, tricalcium phosphate, and tetracalcium oxyphosphate;
[0024] The drug coating is made of at least one of the following materials:
[0025] Pitavastatin, chondroitin sulfate, alendronate sodium, rapamycin and its derivatives coating, paclitaxel coating, everolimus coating, sirolimus coating and mitomycin.
[0026] A second objective of this invention is to provide a method for preparing a tantalum-based oral cavity guided bone regeneration barrier membrane as provided in one objective of this invention.
[0027] To achieve the second objective of this invention, the technical solution adopted by this invention is as follows:
[0028] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane, the method comprising:
[0029] Tantalum-based metals are mechanically pressed into tantalum-based metal films with a thickness of 1μm-30μm.
[0030] The film was annealed at a temperature of 350℃-450℃ for 2 hours.
[0031] The annealed film is cut into the target shape and size using a pulsed laser.
[0032] The cut film was then subjected to ultrasonic cleaning and drying with acetone, anhydrous ethanol and deionized water in sequence to obtain a barrier film.
[0033] To achieve the second objective of this invention, another technical solution adopted by this invention is as follows:
[0034] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane, the method comprising:
[0035] A metal frame is cut from a tantalum-based metal sheet using a pulsed laser. The tantalum-based metal sheet has a thickness of 50μm-100μm and a width of 1mm-2mm.
[0036] A groove of the same thickness as the metal frame is cut in the center of the glass substrate using a pulsed laser, and the metal frame is then embedded into the groove in the glass substrate.
[0037] The glass substrate with the metal frame is placed on a magnetron sputtering substrate platform, and tantalum-based metal is sputtered onto the glass substrate and the metal frame by magnetron sputtering to obtain a tantalum-based metal barrier film with the metal frame. The sputtering thickness of the tantalum-based metal is 1μm-30μm.
[0038] The tantalum-based metal barrier film is separated from the glass substrate and then subjected to ultrasonic cleaning and drying with acetone, anhydrous ethanol and deionized water in sequence to obtain the barrier film.
[0039] To achieve the second objective of this invention, another technical solution adopted by this invention is as follows:
[0040] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane, the method comprising:
[0041] A metal frame is cut from a pure tantalum sheet using a pulsed laser. The pure tantalum sheet has a thickness of 50μm-100μm and a width of 1mm-2mm.
[0042] A groove of the same thickness as the metal frame is cut in the center of the glass substrate using a pulsed laser, and the metal frame is then embedded into the groove in the glass substrate.
[0043] The glass substrate with a metal frame is fixed in a vapor deposition reaction chamber. Pure tantalum is deposited on the glass substrate by reacting H2, Ar and TaCl5 powder to obtain a pure tantalum barrier film with a metal frame. The deposition thickness of the pure tantalum is 1μm-30μm.
[0044] The pure tantalum barrier film is separated from the glass substrate and then subjected to ultrasonic cleaning and drying with acetone, anhydrous ethanol and deionized water in sequence to obtain the barrier film.
[0045] Compared with the prior art, this application has at least the following advantages:
[0046] 1. The barrier membrane provided in this embodiment of the invention is made of tantalum-based metal. Tantalum has excellent biocompatibility and chemical stability, which can ensure that the barrier membrane does not react with the human body during implantation, thus avoiding damage to the membrane structure or the release of substances harmful to the human body. In addition to pure tantalum, the addition of alloying elements titanium and tungsten can improve the strength of the material, the addition of copper can improve the antibacterial properties of the material, and the addition of niobium can improve the oxidation resistance of the material. The above-mentioned tantalum alloys also have excellent biocompatibility and chemical stability.
[0047] 2. Compared with currently used non-absorbable polytetrafluoroethylene (PTFE) membranes and titanium meshes, the tantalum-based metal barrier membrane provided in this embodiment of the invention has better bone-promoting and antibacterial capabilities, which is beneficial to accelerating bone tissue growth and healing and reducing the incidence of inflammation after exposure. Moreover, tantalum has good strength and ductility, and can be made into tantalum membranes that are comparable to or even thinner than aluminum foil. Compared with PTFE membranes, tantalum-based metal barrier membranes have higher mechanical strength and stronger barrier space maintenance capabilities. Compared with titanium meshes, the thickness of tantalum-based metal barrier membranes is less than 50 μm, which facilitates customized cutting by doctors during surgery and secondary removal after surgery. After implantation, it has good flexibility and fit, causes less stimulation to soft tissues, and is less likely to be exposed.
[0048] 3. The barrier membrane provided in this embodiment of the invention has through-pores with a diameter of less than 20 μm. The through-pores can be prepared by high-efficiency and high-quality laser drilling, which on the one hand ensures the transport of proteins, minerals and blood required for osteogenic formation; on the other hand, it also blocks the invasion of bacteria and soft tissue into the osteogenic area; at the same time, the through-pore structure also improves the attachment of osteoblasts on the periosteum side, providing good surface conditions for coating preparation and drug delivery.
[0049] 4. The barrier membrane provided in this embodiment of the invention can be fixed with a metal frame on the side facing the bone tissue; the metal frame improves the structural stability of the barrier membrane after bending, improves the ability to maintain the barrier space, ensures the quantity, quality and appearance of the newly formed bone tissue, and ensures the success rate and aesthetics of dental implants. It is especially suitable for implant restoration with complex shapes and large bone defects.
[0050] 5. In the preparation method provided in the embodiments of the present invention, the mechanical extrusion method has a relatively simple process route and is suitable for mass production of tantalum films; the preparation process does not involve complex reaction conditions, introduces fewer reagents in the preparation process, and has high safety; the laser welding has high precision and low energy input, making it easy to ensure the integrity of the film and the welding precision.
[0051] 6. In the preparation method provided in the embodiments of the present invention, the magnetron sputtering method and the chemical vapor deposition method can omit the welding process between the metal frame and the thin film, and directly form a connection with the metal frame during the thin film forming process; the formed thin film is thinner, the adhesion of the obtained tantalum film is better, and the probability of exposure is reduced. Attached Figure Description
[0052] To more clearly illustrate the technical solution of this application, the drawings used in the description of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0053] Figure 1This is a schematic diagram illustrating the working principle of the GBR technology described in one embodiment of this application;
[0054] Figure 2 This is a schematic diagram of the overall structure of the metal-frame-free barrier membrane according to an embodiment of this application;
[0055] Figure 3 This is a schematic diagram of the overall structure of the barrier membrane with a metal frame according to an embodiment of this application;
[0056] Figure 4 This is a partially enlarged schematic diagram of a microporous unit described in an embodiment of this application;
[0057] Figure 5 This is an overall schematic diagram of several shapes of the metal frame described in one embodiment of this application;
[0058] Figure 6 This is a schematic diagram of the usage process of the barrier membrane described in one embodiment of this application;
[0059] Figure 7 This is a diagram showing the experimental results of the effect of pore size distribution on cell adhesion as described in one embodiment of this application;
[0060] Figure 8 This is a diagram showing the results of a cell adhesion experiment described in one embodiment of this application;
[0061] Figure 9 This is a diagram showing the results of a cell proliferation experiment described in one embodiment of this application;
[0062] Figure 10 This is a schematic diagram of an experimental method for testing the compliance of a barrier membrane according to an embodiment of this application;
[0063] Figure 11 This is a schematic flowchart of the mechanical extrusion method according to an embodiment of this application;
[0064] Figure 12 This is a schematic flowchart of the magnetron sputtering method according to an embodiment of this application;
[0065] Figure 13 This is a schematic flowchart of the chemical vapor deposition method described in one embodiment of this application.
[0066] Explanation of reference numerals in the attached figures:
[0067] 1. Barrier membrane; 2. Filling material; 3. Alveolar bone; 4. Soft tissue; 5. Microporous unit; 6. Through hole; 7. Metal frame; 8. Bone defect area; 9. Regenerated bone tissue; 10. Counterweight; 11. Support platform. Detailed Implementation
[0068] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0069] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0070] In the description of this invention, it should be understood that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, these terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention. Furthermore, the technical features involved in the different embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0071] In a first aspect, the present invention provides a tantalum-based oral cavity guided bone regeneration barrier membrane 1, wherein the barrier membrane 1 is made of tantalum-based metal, the tantalum-based metal including pure tantalum and tantalum alloy; wherein the alloying element in the tantalum alloy includes at least one of niobium, titanium, molybdenum, copper, zinc, tungsten and hafnium; wherein the thickness of the barrier membrane 1 is 1μm-30μm.
[0072] In specific implementation, when the alloying element is niobium, the barrier film 1, by mass percentage, includes 55%-100% (but not 100%) tantalum and 0%-45% (but not 0%) niobium; preferably, it includes 70%-100% (but not 100%) tantalum and 0%-30% (but not 0%) niobium.
[0073] Alternatively, when the alloying element is titanium, the barrier film 1, by mass percentage, comprises 70%-100% (but not 100%) tantalum and 0%-30% (but not 0%) titanium; preferably, it comprises 80%-100% (but not 100%) tantalum and 0%-20% (but not 0%) niobium.
[0074] Alternatively, when the alloying element is molybdenum, copper, zinc, tungsten, or hafnium, the barrier film 1, by mass percentage, comprises 90%-100% (but not 100%) tantalum and 0%-10% (but not 0%) alloying elements; preferably, it comprises 97%-100% (but not 100%) tantalum and 0%-3% (but not 0%) alloying elements.
[0075] In specific implementation, the barrier membrane 1 has multiple through holes 6, each with a diameter of 1μm-20μm, which is used to improve nutrient and blood supply transport while preventing soft tissue cells from entering the barrier space.
[0076] In a specific implementation, the plurality of through holes 6 are located in areas of the barrier membrane 1 other than the central region, wherein the shape of the central region is a regular hexagon; and the plurality of through holes 6 form a plurality of micropore units 5, each of the micropore units 5 having a regular hexagonal shape, the inscribed circle diameter of the regular hexagonal micropore unit 5 being 1mm-1.5mm, and the spacing between two adjacent micropore units 5 being 200μm-400μm; and the spacing between two adjacent through holes 6 within each micropore unit 5 being 30μm-60μm.
[0077] Preferably, the diameter of the inscribed circle of the regular hexagon is 1 / 6 to 1 / 3 of the length of the barrier membrane 1. Since the connection areas between the multiple microporous units 5 of the barrier membrane 1 are not perforated, and a regular hexagonal area is reserved in the central region without perforation, the spatial stability of the barrier membrane 1 can be improved.
[0078] In some embodiments, the orientation of the regular hexagon in the central region differs from that of the regular hexagon in the microporous unit 5. For example, the orientation of the regular hexagon in the central region after rotating 90° is the same as that of the regular hexagon in the microporous unit 5. In some embodiments, the area of the central region is larger than the area of the microporous unit 5.
[0079] For example, such as Figure 4 As shown, Figure 4 This is a partially enlarged schematic diagram of the microporous unit 5. Within the same microporous unit 5, the spacing between multiple through-holes 6 is 50 μm. The outer contour of the microporous unit 5 is a regular hexagon with an inscribed circle diameter of 1 mm. The microporous units 5 are arranged in a honeycomb structure, with an adjacent microporous unit 5 spaced 0.2 mm apart. The microporous units 5 need to be designed to avoid the center, edges, and location of the metal frame 7 of the barrier membrane 1 to ensure strength. The microporous units 5 form weak areas on the membrane, facilitating the surgeon's insertion and fixation during the operation.
[0080] In specific implementations, a metal frame 7 is welded to the barrier membrane 1, and the metal frame 7 is made of the tantalum-based metal; wherein the metal frame 7 has a thickness of 50μm-100μm and a width of 1mm-2mm. The metal frame 7 is welded to the inner side of the barrier membrane 1, that is, the side close to the patient's bone defect area 8, for enhancing the space maintenance capability of the barrier membrane 1. The metal frame 7 is composed of a plurality of strips, and has a shape of a straight line shape, double ¥ shape, double ¥ shape, double wood shape or a customized shape that is beneficial to maintaining the spatial stability of the barrier membrane 1, and the width of the strips is 1mm-2mm. Among them, the metal frame 7 of the barrier membrane 1 has a variety of design modes, which can be specifically selected according to the outer shape of the bone defect area 8.
[0081] Preferably, when the barrier membrane 1 is pure tantalum, the metal frame 7 is pure tantalum, and when the barrier membrane 1 is a tantalum alloy, the metal frame 7 is a tantalum alloy.
[0082] For example, as Figure 5 shown in, Figure 5 are overall schematic views of several shapes of the metal frame. From left to right, the metal frame 7 is sequentially a straight line shape; a double ¥ shape formed by combining and connecting two ¥-shaped structures, which are symmetrical about the center line, and the transversely extending strips are inclined toward the V-shaped strips; a double ¥ shape formed by combining and connecting two ¥-shaped structures through a transverse straight-line strip, and having a symmetrical structure with respect to the straight-line strip; a fence shape formed by combining and connecting an X-shaped structure and two straight-line strips arranged at intervals in the transverse direction; and a double wood shape formed by combining and connecting two wood-shaped structures, which are symmetrical about the center line.
[0083] For example, for a patient with a long and narrow bone defect area 8, a straight-line frame is suitable; for a patient with a wide bone defect area 8, a double wood-shaped frame is suitable. The doctor can make a selection according to the actual situation of the patient.
[0084] In specific implementations, the surface of the barrier membrane 1 is coated with a degradable polymer coating, a ceramic coating or a drug coating, for providing functions such as promoting osteogenesis or antibacterial and anti-inflammation. The degradable polymer coating may at least include the following two situations:
[0085] The first situation: any one of polycaprolactone (PCL), polylactic acid (PLA), polyglycolic acid (PGA), L-polylactic acid (PLLA), polycyanoacrylate (PACA), polyanhydride, polyphosphazene, polydioxanone, poly-hydroxybutyrate, polyhydroxyvalerate or chitosan;
[0086] The second situation: a copolymer of any two or more of polylactic acid (PLA), polycaprolactone (PCL), polyglycolic acid (PGA), L-polylactic acid (PLLA), polycyanoacrylate (PACA) or polydioxanone.
[0087] The ceramic coating may include at least one of hydroxyapatite, tricalcium phosphate, and tetracalcium oxyphosphate; the drug coating may include at least one of pitavastatin, chondroitin sulfate, sodium alendronate, rapamycin and its derivatives, paclitaxel, everolimus, sirolimus, and mitomycin.
[0088] like Figure 1 As shown, Figure 1 This is a schematic diagram illustrating the working principle of the GBR technology, showing the use of the barrier membrane 1 in the alveolar bone 3 according to an embodiment of the present invention. During the procedure, the surgeon uses filler bone 2 to fill the bone defect area 8 of the patient. Then, comparing the outer contour of the patient's alveolar bone 3, the barrier membrane 1 is bent to fit tightly against the upper part of the alveolar bone 3 and fixed. Finally, the outer soft tissue 4 is sutured, completing the placement of the barrier membrane 1. When correctly installed, the barrier membrane 1 will prevent soft tissue 4 from invading the bone repair area, while the perforations 6 on its surface will enhance blood supply, protein, and mineral transport.
[0089] Please continue reading. Figure 6 , Figure 6 This is a schematic diagram illustrating the usage process of the barrier membrane according to an embodiment of the present invention. The expected repair process of the barrier membrane 1 involved in bone regeneration in the present invention is as follows: Figure 6 As shown, the barrier membrane 1 needs to completely cover the bone defect area 8 during use. The membrane needs to be tightly attached to the alveolar bone 3 and fixed around it. After the bone repair is completed, the barrier membrane 1 is removed, and the regenerated bone tissue 9 is formed and has sufficient strength.
[0090] In related technologies, the preparation of metal GBR films using traditional processing methods requires multiple passes of heating and rolling, heat treatment, surface treatment, and welding and cutting to obtain metal films with customized structures and thicknesses ranging from 10μm to 100μm. This involves numerous steps and a lengthy process, making it difficult to adapt to the rapid and personalized preparation of GBR films. Tantalum, with its high reactivity and ability to react with various substances at high temperatures, presents even greater challenges to its preparation process. Therefore, current limitations in the preparation of tantalum metal films restrict the development of tantalum-based metal barrier films.
[0091] In view of this, in a second aspect, the present invention provides three methods for preparing tantalum-based oral guided bone regeneration barrier membranes, including a combined mechanical extrusion and laser cutting method, a magnetron sputtering method, and a chemical vapor deposition method.
[0092] In practice:
[0093] This invention provides a method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane as provided in the first aspect of this invention. This method is based on a preparation method combining mechanical extrusion and laser cutting, and includes the following steps:
[0094] S1. Mechanically press tantalum-based metal into a tantalum-based metal film with a thickness of 1μm-30μm;
[0095] S2. Anneal the film at a temperature of 350℃-450℃ for 2 hours to enhance the toughness of the film.
[0096] S3. Use a pulsed laser to cut the annealed film into the target shape and size, and use a pulsed laser to cut a tantalum-based metal sheet with a thickness of 50μm-100μm to form a metal frame 7;
[0097] The process parameters for laser cutting are as follows:
[0098] The laser wavelength is 0.8μm-1.2μm, preferably 1.06μm; the spot diameter is 0.05mm-0.2mm, preferably 0.1mm; the pulse width is 80ns-150ns, preferably 100ns; the pulse energy is 5mJ-30mJ, preferably 10mJ; the repetition frequency is 1kHz; and the cutting speed is 5m / min-20m / min, preferably 10m / min.
[0099] S4. The cut film and metal frame 7 are ultrasonically cleaned in sequence with acetone, anhydrous ethanol and deionized water, and then dried at 25℃-50℃.
[0100] S5. Use a pulsed laser to prepare through holes 6 with a pore size of 1μm-20μm on the dried film. The arrangement of the through holes 6 can be referred to the above.
[0101] The laser used is a pulsed fiber laser with a wavelength of 0.8μm-1.2μm, preferably 1.06μm, a spot diameter of 0.005mm-0.02mm, preferably 0.02mm, a pulse width of 1ns, a pulse energy of 0.5mJ-3mJ, preferably 1mJ, and a repetition frequency of 5kHz-20kHz, preferably 10kHz.
[0102] S6. Using laser or resistance spot welding, weld the metal frame 7 obtained in step S4 onto the perforated film to obtain the barrier film 1.
[0103] The laser used is a pulsed fiber laser with a wavelength of 0.8-1.2μm, preferably 1.06μm; a spot diameter of 0.05mm-0.2mm, preferably 0.1mm; a pulse width of 1ms; a pulse energy of 0.5-3J, preferably 1J; and a repetition frequency of 0.5kHz-5kHz, preferably 1kHz.
[0104] The combined mechanical extrusion and laser cutting method provided by this invention has a relatively simple process route, which is suitable for mass production of tantalum films. The preparation process does not involve complex reaction conditions, introduces fewer reagents in the preparation process, and has high safety. The laser welding has high precision and low energy input, which makes it easy to ensure the integrity of the film and the welding precision.
[0105] In practice:
[0106] This invention also provides a method for preparing a tantalum-based oral guided bone regeneration barrier membrane as provided in the first aspect of this invention. This method is based on magnetron sputtering and includes the following steps:
[0107] S10. Using a pulsed laser, a tantalum-based metal sheet is cut into a metal frame 7, wherein the thickness of the tantalum-based metal sheet is 50μm-100μm and the width is 1mm-2mm.
[0108] The laser wavelength used is 0.8μm-1.2μm, preferably 1.06μm; the spot diameter is 0.05mm-0.2mm, preferably 0.1mm; the pulse width is 100ns; the pulse energy is 5mJ-30mJ, preferably 10mJ; the repetition frequency is 0.5kHz-5kHz, preferably 1kHz; and the cutting speed is 5m / min-20m / min, preferably 10m / min.
[0109] S20. Using the metal frame 7 as the outline, a groove of the same thickness as the metal frame 7 is cut in the center of the glass substrate using a pulsed laser, and the metal frame 7 is embedded into the groove of the glass substrate.
[0110] S30. The glass substrate with the metal frame 7 is placed on a magnetron sputtering substrate platform, and tantalum-based metal is sputtered onto the glass substrate and the metal frame 7 by magnetron sputtering to obtain a tantalum-based metal barrier film 1 with the metal frame 7.
[0111] The process parameters for sputtering are as follows: working gas pressure 0.2 Pa - 1.0 Pa, preferably 0.5 Pa; tantalum-based metal with a diameter of 30 mm - 100 mm, preferably 50 mm, and a thickness of 1 mm - 10 mm, preferably 3 mm; substrate heating temperature 700℃ - 900℃, preferably 800℃; power 200 W - 500 W, preferably 300 W; and sputtering thickness of the tantalum-based metal 1 μm - 30 μm.
[0112] S40. Separate the tantalum-based metal barrier film 1 from the glass substrate, and then ultrasonically clean it with acetone, anhydrous ethanol and deionized water in sequence, and dry it at 25℃-50℃.
[0113] S50. Use a pulsed laser to prepare through holes 6 with a pore size of 1μm-20μm on the dried tantalum-based metal barrier film 1. The arrangement of the through holes 6 can be referred to the above to obtain the barrier film 1.
[0114] The laser used is a pulsed fiber laser with a wavelength of 0.8μm-1.2μm, preferably 1.06μm; a spot diameter of 0.005mm-0.02mm, preferably 0.02mm; a pulse width of 1ns; a pulse energy of 0.5mJ-3mJ, preferably 1mJ; and a repetition frequency of 5kHz-20kHz, preferably 10kHz.
[0115] In practice:
[0116] The present invention also provides a method for preparing a tantalum-based oral guided bone regeneration barrier membrane as provided in the first aspect of the present invention. This method is based on a chemical vapor deposition preparation method and includes the following steps:
[0117] S100. Using a pulsed laser, a pure tantalum sheet is cut into a metal frame 7, wherein the pure tantalum sheet has a thickness of 50μm-100μm and a width of 1mm-2mm.
[0118] The laser wavelength used is 0.8μm-1.2μm, preferably 1.06μm; the spot diameter is 0.05mm-0.2mm, preferably 0.1mm; the pulse width is 100ns; the pulse energy is 5mJ-30mJ, preferably 10mJ; the repetition frequency is 0.5kHz-5kHz, preferably 1kHz; and the cutting speed is 5m / min-20m / min, preferably 10m / min.
[0119] S200. Using the metal frame 7 as the outline, a groove of the same thickness as the metal frame 7 is cut in the center of the glass substrate using a pulsed laser, and the metal frame 7 is embedded into the groove of the glass substrate.
[0120] S300. The glass substrate with metal frame 7 is fixed in the vapor deposition reaction chamber. Pure tantalum is deposited on the glass substrate by reacting H2, Ar and TaCl5 powder to obtain a pure tantalum barrier film 1 with metal frame 7.
[0121] The process parameters for chemical vapor deposition are as follows: powder delivery rate of 0.5 g / min-1 g / min, preferably 1 g / min; gas flow rate of 50 ml / min-500 ml / min, preferably 300 ml / min; reaction temperature of 1200℃-1350℃, preferably 1300℃; reaction pressure of 5 kPa-15 kPa, preferably 8 kPa; deposition time of 2 h-8 h, preferably 2 h; and deposition thickness of pure tantalum of 1 μm-30 μm.
[0122] S400: Separate the pure tantalum barrier film 1 from the glass substrate, and then ultrasonically clean it in sequence with acetone, anhydrous ethanol and deionized water, and dry it at 25℃-50℃.
[0123] S500. Use a pulsed laser to prepare through holes 6 with a pore size of 1μm-20μm on the dried pure tantalum barrier film 1. The arrangement of the through holes 6 can be referred to the above to obtain the barrier film 1.
[0124] The laser used is a pulsed fiber laser with a wavelength of 0.8μm-1.2μm, preferably 1.06μm; a spot diameter of 0.05mm-0.2mm, preferably 0.1mm; a pulse width of 1ns; a pulse energy of 0.5mJ-3mJ, preferably 1mJ; and a repetition frequency of 5kHz-20kHz, preferably 10kHz.
[0125] In summary, magnetron sputtering and chemical vapor deposition can eliminate the welding process between the metal frame 7 and the thin film, and directly form a connection with the metal frame 7 during the thin film forming process; the formed thin film is thinner, the resulting barrier film 1 has better adhesion, and the probability of exposure is reduced.
[0126] In addition, laser drilling is a low-energy-input drilling method; compared with traditional drilling methods, it produces holes with better uniformity, higher drilling efficiency, and higher precision. Furthermore, the array distribution of holes can be controlled by computer programs, ensuring the quality of the through holes on the tantalum film surface and reducing the possibility of defects during the drilling process.
[0127] In conjunction with the above embodiments, in specific implementation, a coating can be applied to the surface of the barrier film 1, that is, after steps S6, S50, and S500, the following may also be included:
[0128] S001. The barrier film 1 obtained in step S6, step S50, or step S500 is immersed in a coating material melt and heated, kept at a constant temperature, evaporated, or prepared by other coating methods to obtain a surface coating, thus obtaining a multifunctional barrier film 1. The coating material melt can refer to the coating material described above.
[0129] As a specific explanation of this embodiment, the prepared barrier membrane 1 can be applied. Specifically, after preparing the barrier membrane 1, it is sterilized at high temperature, then wrapped in sterile paper and placed in a vacuum bag. Before use, the vacuum bag is opened, the sterile paper is used to compare the membrane in the patient's oral cavity, and the sterile paper is cut into a suitable shape to match the space of the bone defect; then, using the cut sterile paper as a template, the tantalum-based oral guided bone regeneration barrier membrane 1 is cut into a suitable shape to match the space of the bone defect.
[0130] For example:
[0131] The method of using the tantalum-based oral cavity-guided bone regeneration barrier membrane provided in this embodiment of the invention includes:
[0132] (1) Take out one piece of sterile paper wrapped with barrier membrane 1 and cut it according to the specified size using ophthalmic scissors;
[0133] (2) Fit the sterilized paper cut in step one to the affected area that has been filled with bone powder, and further trim the shape;
[0134] (3) Take out the sterilized paper and attach the barrier film 1 to it. Using the trimmed sterilized paper as a template, use ophthalmic scissors to trim the barrier film 1 into a shape that fits the affected area.
[0135] (4) Apply the barrier membrane 1 to the affected area, locate and mark the suitable position for placing the fixation screws;
[0136] (5) Use a fixing screw to penetrate the barrier membrane 1 and nail it into the alveolar bone to fix the barrier membrane 1.
[0137] To enable those skilled in the art to more clearly understand the present invention, the following embodiments will be used to provide a detailed description of a tantalum-based oral cavity guided bone regeneration barrier membrane and its preparation method.
[0138] Example 1
[0139] like Figure 2 As shown, Figure 2 This is a schematic diagram of the overall structure of a barrier membrane without a metal frame.
[0140] Specifically, in this embodiment, a method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane includes the following steps:
[0141] 1) Pure tantalum was pressed into a 20μm thick film and annealed at 400℃ for 2h;
[0142] 2) The thin film is cut into rounded rectangles with dimensions of 30mm*20mm and a corner radius R1 of 1mm using a pulsed fiber laser. The pulsed fiber laser has a wavelength of 1.06μm, a spot diameter of 0.1mm, a pulse width of 100ns, a pulse energy of 10mJ, a repetition frequency of 1kHz, and a cutting speed of 10m / min.
[0143] 3) The prepared film of the specified size was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10 min each, and dried at 25°C for 2 h.
[0144] 4) Through holes 6 are fabricated on the dried film using pulsed laser. The through holes 6 are periodically arranged into a regular hexagonal micropore unit 5. Each micropore unit 5 contains several through holes 6. The diameter of the through holes 6 is 15μm. The diameter of the inscribed circle of the micropore unit 5 is 1mm. The spacing between the micropore units 5 is 0.2mm.
[0145] The laser used has a wavelength of 1.06 μm, a spot diameter of 0.01 mm, a pulse width of 1 ns, a pulse energy of 1 mJ, and a repetition frequency of 10 kHz.
[0146] Among them, by using a scanning galvanometer, 100 through holes with a diameter of 15 μm can be prepared per second on a 20 μm thick pure tantalum film;
[0147] 5) Dissolve PLA in 5% acetone and stir at 50°C for 2 hours. Immerse the membrane after the perforation treatment in step 4 into the acetone and continue to keep it at that temperature for 2 hours. Remove the barrier membrane 1 and evaporate it in a drying oven at 100°C for 3 hours to complete the surface coating preparation, obtaining the following... Figure 2 The barrier membrane 1 shown.
[0148] Example 2
[0149] like Figure 3 As shown, Figure 3 This is a schematic diagram of the overall structure of the barrier membrane with a metal frame. In this embodiment, the barrier membrane 1 has a thickness of 30 μm, the diameter of the through holes 6 on the membrane is 20 μm, and a double-¥-shaped reinforcing metal frame 7 is welded to the inner side of the barrier membrane 1, located in the middle of the membrane, with a thickness of 80 μm. Other aspects are the same as in Embodiment 1.
[0150] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane includes the following steps:
[0151] 11) Pure tantalum was pressed into a 30μm thick film and annealed at 350℃ for 2h;
[0152] 12) The thin film is cut into rounded rectangles with dimensions of 30mm*20mm and a corner radius R1 of 1mm using a pulsed fiber laser. The pulsed fiber laser has a wavelength of 1.06μm, a spot diameter of 0.1mm, a pulse width of 100ns, a pulse energy of 10mJ, a repetition frequency of 1kHz, and a cutting speed of 10m / min.
[0153] 13) The prepared membrane material of the specified size was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10 min each, and dried at 25°C for 2 h.
[0154] 14) A through hole 6 with a diameter of 20 μm was prepared on the dried film using a pulsed laser. The laser wavelength was 1.06 μm, the spot diameter was 0.01 mm, the pulse width was 1 ns, the pulse energy was 1 mJ, and the repetition frequency was 10 kHz.
[0155] Among them, by using a scanning galvanometer, 100 through holes with a diameter of 20 μm can be prepared per second on a 30 μm thick pure tantalum film;
[0156] 15) Weld the metal frame 7 onto the perforated film using laser or resistance spot welding; cut a double-¥-shaped tantalum strip with a thickness of 80μm and a width of 1.5mm using laser. The laser spot welding uses a pulsed fiber laser with a wavelength of 1.06μm, a spot diameter of 0.1mm, a pulse width of 1ms, a pulse energy of 1J, and a repetition frequency of 1kHz. The laser acts on one side of the tantalum strip, and the weld points are evenly distributed on the tantalum strip.
[0157] 16) Dissolve PLA / PCL in 5% acetone at a mass ratio of 4:1, stir at 50°C for 2 hours, immerse the film treated in step 15 in the solution and continue to keep it at that temperature for 2 hours. Remove the barrier film 1 and evaporate it in a drying oven at 100°C for 3 hours to complete the surface coating preparation, obtaining the following... Figure 3 The barrier membrane 1 shown.
[0158] Example 3
[0159] Please see Figure 11 , Figure 11 The flowchart of the mechanical extrusion method includes five steps: a) film extrusion, b) laser cutting of the frame, c) laser drilling, d) laser spot welding, and e) sterilization and packaging.
[0160] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane includes the following steps:
[0161] 21) For example Figure 11 (a) Pure tantalum was mechanically extruded into a film with a thickness of 20 μm and annealed at 400 °C for 2 h;
[0162] 22) For example Figure 11 (b) The thin film and the 100μm tantalum sheet were cut into the required size and shape using a pulsed fiber laser, which were used as the thin film and metal frame 7 parts of the barrier film 1 product, respectively. The 20μm thick thin film was cut into a rounded rectangular film with a size of 30mm*20mm, and the sheet was cut into a double "¥" shaped metal frame 7 with a width of 2mm. The laser wavelength used was 1.06μm, the spot diameter was 0.1mm, the pulse width was 100ns, the pulse energy was 10mJ, the repetition frequency was 1kHz, and the cutting speed was 10m / min.
[0163] 23) The film and metal frame 7 obtained in step 21 were ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 20 min in sequence, and dried at 25°C for 2 h.
[0164] 24) For example Figure 11 (c) Fabrication on the dried film using pulsed laser Figure 2The through-hole 6 shown has a diameter of 20 μm. The laser used is a pulsed fiber laser with a wavelength of 1.06 μm, a spot diameter of 0.02 mm, a pulse width of 1 ns, a pulse energy of 1 mJ, and a repetition frequency of 10 kHz.
[0165] 25) For example Figure 11 (d) A metal frame 7 is welded onto the perforated film using laser spot welding. A pulsed fiber laser is used with a wavelength of 1.06 μm, a spot diameter of 0.1 mm, a pulse width of 1 ms, a pulse energy of 0.5 J, and a repetition frequency of 1 kHz. The laser acts on one side of the tantalum frame, and the weld points are evenly distributed around the periphery of the frame to obtain the barrier film 1.
[0166] Example 4
[0167] The main difference from Example 1, Example 2, or Example 3 is that the parameters of the thin film are changed, while the remaining steps and principles are the same; the specific parameters of the thin film are shown in Table 1:
[0168] Table 1 (Parameter Data Table for Thin Films):
[0169]
[0170]
[0171] Table 1
[0172] Example 5
[0173] The main difference from Embodiment 2 or Embodiment 3 is that the parameters of the metal frame 7 are changed, while the remaining steps and principles are the same; the specific parameters of the metal frame 7 are shown in Table 2:
[0174] Table 2 (Parameter Data Table for Metal Frames):
[0175]
[0176] Table 2
[0177] Example 6
[0178] The main difference from Embodiment 1, Embodiment 2, or Embodiment 3 is that the parameters of the pulsed fiber laser cutting process are changed, while the remaining steps and principles remain the same; the specific parameters of the cutting process are shown in Table 3.
[0179] Table 3 (Cut-off parameter data table for pulsed fiber laser):
[0180]
[0181] Table 3
[0182] Example 7
[0183] The main difference from Embodiment 1, Embodiment 2, or Embodiment 3 is that the parameters of the drilling process using pulsed fiber laser are changed, while the remaining steps and principles remain the same; the specific parameters of the drilling process are shown in Table 4.
[0184] Table 4 (Drilling Parameter Data Table for Pulsed Fiber Laser):
[0185] 0.8 0.005 0.5 5 1.2 0.02 3 20
[0186] Table 4
[0187] Example 8
[0188] The main difference from Example 2 or Example 3 is that the welding process parameters of laser spot welding are changed, while the remaining steps and principles remain the same; the specific welding process parameters are shown in Table 5.
[0189] Table 5 (Welding parameter data table for laser spot welding):
[0190] 0.8 0.05 1 0.5 1.2 0.2 3 5
[0191] Table 5
[0192] Example 9
[0193] Prepared by magnetron sputtering and laser cutting Figure 3 The barrier membrane with a metal frame is shown.
[0194] The steps are as follows Figure 12 As shown, Figure 12 This is a schematic diagram of the steps of magnetron sputtering; a) laser cutting frame, b) inlay frame, c) magnetron sputtering film formation, d) laser drilling, e) sterilization and packaging.
[0195] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane includes the following steps:
[0196] 31) Unlike the preparation of the metal frame 7 in step 22 of Example 3, the tantalum frame has a thickness of 80 μm and is in the form of a straight line;
[0197] 32) For example Figure 12 (b) Take a clean and flat glass substrate, and cut a groove of the same thickness as the tantalum frame in the center of the glass substrate with a silicon wafer cutter, using the tantalum frame as the outline in step 31, and embed the tantalum frame into the substrate.
[0198] 33) For example Figure 12(c) The glass substrate with tantalum frame obtained in step 32 is placed on the magnetron sputtering substrate platform. The tantalum-based metal target is sputtered onto the glass substrate and the prefabricated tantalum frame by magnetron sputtering. Sputtering is carried out in an argon atmosphere for 1.5 hours with a working pressure of 0.5 Pa. The target diameter is 50 mm and the thickness is 3 mm. The substrate heating temperature is 800 °C and the power is 300 W.
[0199] 34) Separate the tantalum film with tantalum framework obtained in step 33 from the glass substrate, and ultrasonically clean it in acetone, anhydrous ethanol and deionized water for 20 min in sequence, and dry it at 40°C for 2 h.
[0200] 35) A through hole 6 with a diameter of 20 μm was prepared on the tantalum film obtained in step 34 using a pulsed laser. The laser used was a pulsed fiber laser with a wavelength of 1.06 μm, a spot diameter of 0.02 mm, a pulse width of 1 ns, a pulse energy of 1 mJ, and a repetition frequency of 10 kHz, to obtain the barrier film 1.
[0201] Example 10
[0202] The main difference from Example 9 is that the parameters of the magnetron sputtering process are changed, while the remaining steps are the same as the principle; the specific parameters of the magnetron sputtering process are shown in Table 6:
[0203] Table 6 (Parameter Data Table for Magnetron Sputtering Process):
[0204] 0.2 70 5 775 320 1.0 100 2 700 200 0.8 30 10 900 500
[0205] Table 6
[0206] Example 11
[0207] Prepared by chemical vapor deposition and laser cutting Figure 3 The barrier membrane with a metal frame is shown.
[0208] The steps are as follows Figure 13 As shown, Figure 13 This is a schematic diagram of the steps in chemical vapor deposition (CVD); a) laser cutting the frame, b) embedding the frame, c) CVD film formation, d) laser drilling, and e) sterilization and packaging.
[0209] A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane includes the following steps:
[0210] 41) Unlike the preparation of the metal frame 7 in step 22 of Example 3, the tantalum frame has a thickness of 50 μm and is of the double K type;
[0211] 42) Take a clean and flat pure silicon substrate, and cut a groove of the same thickness as the tantalum frame in the center of the glass substrate with a silicon wafer cutter, using the tantalum frame obtained in step 41 as the outline, and embed the tantalum frame into the substrate.
[0212] 43) For example Figure 13 (c) The glass substrate with tantalum frame obtained in step 42 is fixed in the vapor deposition reaction chamber. Pure Ta is deposited on the substrate by reacting H2 and Ar gas with TaCl5 powder. The powder delivery rate is 1 g / min, the gas flow rate is 300 ml / min, the reaction temperature is 1300℃, the reaction pressure is 8 kPa, and the deposition time is 2 h.
[0213] 44) Separate the tantalum film with tantalum framework obtained in step 43 from the glass substrate, and ultrasonically clean it in acetone, anhydrous ethanol and deionized water for 20 min in sequence, and dry it at 50°C for 2 h.
[0214] 45) A through hole 6 is prepared on the tantalum film obtained in step 44 using a pulsed laser. The hole diameter is 20 μm. The laser used is a pulsed fiber laser with a wavelength of 1.06 μm, a spot diameter of 0.02 mm, a pulse width of 1 ns, a pulse energy of 1 mJ, and a repetition frequency of 10 kHz, to obtain the barrier film 1.
[0215] Example 12
[0216] The main difference from Example 11 is that the parameters of the chemical vapor deposition process are changed, while the remaining steps are the same as the principle; the specific parameters of the chemical vapor deposition process are shown in Table 7:
[0217] Table 7 (Parameter Data Table for Chemical Vapor Deposition Process):
[0218]
[0219] Table 7
[0220] The following are the performance tests performed on the barrier membrane 1 provided in the embodiments of the present invention:
[0221] Test Example 1
[0222] Experiments were conducted to investigate the effect of barrier membrane pore size distribution on cell adhesion ability.
[0223] Barrier membrane No. 1, with 6 pores of 20 μm diameter at 50 μm intervals, and control membrane No. 2, with 6 pores of 40 μm diameter at 250 μm intervals, were cut into 1 cm * 1.5 cm rectangular pieces in the micropore area. The concentration of MC3T3-E1 cells was 10⁶ cells / cm². 3 3 ml of cell-containing culture medium was uniformly infiltrated onto the membrane material, and cultured for 3 days and 1 week, respectively. The resulting membrane structures were treated with fluorescent staining and observed under a fluorescence microscope. Figure 7The experimental results diagram showing the effect of pore size distribution on cell attachment show that cells preferentially attach near the through-hole 6, and the through-hole 6 configuration with a pore size of 20 μm and a spacing of 50 μm has better cell attachment ability. That is, the cell attachment and proliferation of the barrier membrane 1 of the present invention is better than that of the control membrane 2.
[0224] Test Example 2
[0225] Cell adhesion experiments using tantalum-based metals:
[0226] Disks with a diameter of 10 mm and a thickness of 1 mm were fabricated from pure tantalum and titanium alloy (Ti6Al4V). The titanium alloy and pure tantalum disks were placed in 24-well plates (Corning, Corning, NY, USA), and MC3T3-E1 cells and hBMSCs cells were cultured at 1.2 × 10⁻⁶ cells per well. 4 The concentration of cells / well was inoculated along with the culture medium. After incubation for 1, 2, 4, and 8 hours, the samples were washed with culture medium and transferred to new 24-well plates containing 600 μL of culture medium. Cell adhesion was assessed using a cell counting kit (CCK8, DOJINDO, Japan). Figure 8 The results of the cell adhesion experiment shown in the figure demonstrate that pure tantalum metal exhibits superior cell adhesion compared to titanium alloy, making it more suitable for guiding the performance requirements of bone regeneration membranes.
[0227] Test Example 3
[0228] Cell proliferation experiments using tantalum-based metals:
[0229] Disks with a diameter of 10 mm and a thickness of 1 mm were fabricated from pure tantalum and titanium alloy (Ti6Al4V). The titanium alloy and pure tantalum disks were placed in 24-well plates (Corning, Corning, NY, USA), and MC3T3-E1 cells and hBMSCs cells were cultured at 1 × 10⁻⁶ cells per well. 4 Cells were inoculated at a concentration of [number] cells / mL (600 μL per sample) along with the culture medium. Cell proliferation was assessed at 24, 48, 72, 96, and 120 h using the same method as in Test Example 2. Figure 9 The results of the cell proliferation experiment shown in the figure indicate that, within 120 hours, pure tantalum metal exhibited superior cell proliferation properties compared to titanium alloy, which better meets the performance requirements of guiding bone regeneration membranes.
[0230] Test Example 4
[0231] Mechanical properties and adhesion of barrier membrane 1 were tested:
[0232] Barrier film 1 as in Example 2 was prepared using pure tantalum, while barrier film 1 was also prepared using a tantalum alloy (80% Ta, 20% Nb) with the same design parameters. Figure 10 As shown, Figure 10 This is a schematic diagram of the experimental method for testing the flexibility of the barrier membrane. Using a three-point bend model, the two sides of the barrier membrane 1 are overlapped onto the support platform 11, with the distance L between the support points being 1 / 2 (15 mm) of the membrane length. A counterweight 10 is suspended in the middle of the membrane, and the weight is controlled to bend the membrane to angles of 120°, 90°, 60°, and 30° respectively. The mass of the counterweight is measured to test the bending resistance of the barrier membrane 1. After releasing the counterweight, the rebound angle is measured to test the flexibility, i.e., the adhesion, of the barrier membrane 1.
[0233] The experimental results are shown in Table 8 below, with the rebound angle converted to °. As can be seen from the table, the rebound angle (angle of the rebounded membrane - angle of the theoretically bent membrane) is less than 3% of the theoretical bending angle (180° - angle of the theoretically bent membrane), indicating that this barrier membrane 1 has strong adhesion; simultaneously, this product…
[0234] A force of over 5N is required to bend it to 120°, indicating that this barrier membrane 1 has strong bending resistance. Table 8 (Mechanical test data results):
[0235] Rebound angle (°) 1.37±0.24 1.62±0.12 2.16±0.48 2.89±0.77 Counterweight mass (g) 672±129 810±148 854±78 879±175
[0236] Table 8
[0237] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0238] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0239] The foregoing has provided a detailed description of a tantalum-based oral cavity guided bone regeneration barrier membrane and its preparation method. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as limiting the present invention.
Claims
1. A tantalum-based oral cavity-guided bone regeneration barrier membrane, characterized in that, The barrier film is made of tantalum-based metal, which includes pure tantalum and tantalum alloys; wherein the alloying element in the tantalum alloy includes at least one of niobium, titanium, molybdenum, copper, zinc, tungsten and hafnium; The surface of the barrier membrane is coated with a biodegradable polymer coating, a ceramic coating, or a drug coating; wherein... The biodegradable polymer coating is made of at least one of the following materials: Polycaprolactone, polyhydroxyacetic acid, L-polylactic acid, polycyanoacrylate, polyanhydride, polyphosphononitrile, polydioxane, polyhydroxybutyrate, polyhydroxyvalerate and chitosan; The ceramic coating is made of at least one of the following materials: Hydroxyapatite, tricalcium phosphate, and tetracalcium oxyphosphate; The drug coating is made of at least one of the following materials: Pitavastatin, chondroitin sulfate, alendronate sodium, paclitaxel coating, everolimus coating, sirolimus coating, and mitomycin; The barrier membrane has a thickness of 1μm-30μm and multiple pores are formed on it, each pore having a diameter of 1μm-20μm. The pores are configured to allow proteins, minerals and blood required for osteogenic formation to pass through, while blocking soft tissue cells and bacteria from invading the osteogenic area. The plurality of vias are located in areas of the barrier membrane other than the central region, wherein the central region has a regular hexagonal shape; and, The plurality of through holes form a plurality of micropore units, each micropore unit having a regular hexagonal shape and an inscribed circle diameter of 1 mm-1.5 mm, and the spacing between two adjacent micropore units being 200 μm-400 μm; and the spacing between two adjacent through holes within each micropore unit being 30 μm-60 μm; A metal frame is welded onto the barrier membrane, and the metal frame is made of the tantalum-based metal; wherein the thickness of the metal frame is 50μm-100μm and the width is 1mm-2mm.
2. The tantalum-based oral cavity-guided bone regeneration barrier membrane according to claim 1, characterized in that, When the alloying element is niobium, the barrier film, by mass percentage, comprises 55%-100% tantalum (but not equal to 100%) and 0%-45% niobium (but not equal to 0%); or, When the alloying element is titanium, the barrier film, by mass percentage, comprises 70%-100% tantalum (but not equal to 100%) and 0%-30% titanium (but not equal to 0%); or, When the alloying element is molybdenum, copper, zinc, tungsten or hafnium, the barrier film, by mass percentage, includes 90%-100% tantalum but not equal to 100% tantalum content and 0%-10% alloying element but not equal to 0% alloying element content.
3. The tantalum-based oral cavity guided bone regeneration barrier membrane according to claim 1, characterized in that, The metal frame includes any one or a combination of multiple types such as the straight type, double ¥ type, double ¥ type, and double wood type.
4. A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane as described in any one of claims 1-3, characterized in that, The method includes: Tantalum-based metals are mechanically pressed into tantalum-based metal films with a thickness of 1μm-30μm. The film was annealed at a temperature of 350℃-450℃ for 2 hours. The annealed film was cut into the target shape and size using a pulsed laser; and a metal frame was cut from a tantalum-based metal sheet using a pulsed laser. The cut film was then ultrasonically cleaned and dried in acetone, anhydrous ethanol and deionized water in sequence. Through-holes were fabricated on dried thin films using pulsed lasers. The metal frame is welded onto the perforated film using laser or resistance spot welding to obtain the barrier film.
5. A method for preparing a tantalum-based oral cavity guided bone regeneration barrier membrane as described in any one of claims 1-3, characterized in that, The method includes: A metal frame is cut from a tantalum-based metal sheet using a pulsed laser. The tantalum-based metal sheet has a thickness of 50μm-100μm and a width of 1mm-2mm. A groove of the same thickness as the metal frame is cut in the center of the glass substrate using a pulsed laser, and the metal frame is then embedded into the groove in the glass substrate. The glass substrate with the metal frame is placed on a magnetron sputtering substrate platform, and tantalum-based metal is sputtered onto the glass substrate and the metal frame by magnetron sputtering to obtain a tantalum-based metal barrier film with the metal frame. The sputtering thickness of the tantalum-based metal is 1μm-30μm. The tantalum-based metal barrier film is separated from the glass substrate and then subjected to ultrasonic cleaning and drying with acetone, anhydrous ethanol and deionized water in sequence. Through holes are then prepared on the dried film using a pulsed laser to obtain the barrier film.
6. A method for preparing a tantalum-based oral cavity-guided bone regeneration barrier membrane as described in any one of claims 1-3, characterized in that, The method includes: A metal frame is cut from a pure tantalum sheet using a pulsed laser. The pure tantalum sheet has a thickness of 50μm-100μm and a width of 1mm-2mm. A groove of the same thickness as the metal frame is cut in the center of the glass substrate using a pulsed laser, and the metal frame is then embedded into the groove in the glass substrate. The glass substrate with a metal frame is fixed in a vapor deposition reaction chamber. Pure tantalum is deposited on the glass substrate by reacting H2, Ar and TaCl5 powder to obtain a pure tantalum barrier film with a metal frame. The deposition thickness of the pure tantalum is 1μm-30μm. The pure tantalum barrier film is separated from the glass substrate and then subjected to ultrasonic cleaning and drying with acetone, anhydrous ethanol and deionized water in sequence. Through holes are then prepared on the dried film using a pulsed laser to obtain the barrier film.
Citation Information
Patent Citations
Degradable pure magnesium or magnesium alloy oral biological barrier membrane and preparation method thereof
CN114225120A
Medical tantalum alloy and preparation method and application thereof
CN116121614A
Electroactive titanium stent reinforced composite membrane for bone defect repair
CN217696978U
